2004
DOI: 10.1177/0021998304040555
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Tensile and Shear Behavior of Macro Fiber Composite Actuators

Abstract: The Macro Fiber Composite (MFC) actuator, developed at the NASA Langley Research Center, offers much higher flexibility and induced strain levels (~2000μσ, peak-to-peak) than its monolithic piezoceramic predecessors. The focus of this work is twofold; to measure the four independent linear elastic engineering constants of the orthotropic MFC actuator under short-circuit electrical boundary conditions using standard tensile testing procedures, and to use these experimental results to characterize the nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 6 publications
6
77
0
Order By: Relevance
“…This arrangement results in a highly orthotropic transducer element with larger flexibility perpendicular to the working direction compared to a monolithic piezoelectric wafer. The best know representatives of this group are the active fiber composite (AFC) [5] and the Macro Fiber Composite (MFC) [6].…”
Section: Models For Piezoelectric Elements With Idementioning
confidence: 99%
“…This arrangement results in a highly orthotropic transducer element with larger flexibility perpendicular to the working direction compared to a monolithic piezoelectric wafer. The best know representatives of this group are the active fiber composite (AFC) [5] and the Macro Fiber Composite (MFC) [6].…”
Section: Models For Piezoelectric Elements With Idementioning
confidence: 99%
“…In the early constitutive modeling efforts for 33-mode MFCs, Williams et al (2002Williams et al ( , 2004aWilliams et al ( , 2004b presented an experimentally validated model for equivalent thermal expansion and mechanical properties of MFCs using modified classical mixing rules. Deraemaeker et al (2009) reported the mixing rules-based calculations of the equivalent parameters and compared with manufacturer's data and experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The MFC actuator used to excite broadband waves is a flexible actuator developed in NASA Langley Research Center and commercialized in Smart Material Corp. (14) As shown in Fig. 1, the MFC consists of many thin rectangular PZT fibers sandwiched between layers of epoxy adhesive and polyimide film with electrodes.…”
Section: System Configurationmentioning
confidence: 99%
“…However, the authors have succeeded in receiving ultrasonic waves by using fiber Bragg grating (FBG) sensors that are a kind of optical fiber sensors (11)~ (13) . On the other hand, macro fiber composite (MFC) actuators developed in NASA consist of a lot of thin PZT fibers (14) and can be used as a generator of ultrasonic waves (15) . These components do not have the resonant frequency and have high directional characteristic because both of them are fibrous and flexible.…”
Section: Introductionmentioning
confidence: 99%